SPECTROPHOTOMETRIC SENSITIVITY STUDY OF CHROME (III) AND CHROME (VI) - Rodríguez P., Carlos (2002)
By using the criterions of sensibility of IUPAC, we had determinad the sensibility far chromic (III) and (VI) from solution of its differents salts. We found that ion chromic (VI) in the form ion chromate is much sensible than chromic (III).